In Season Exploring the logistics of planning a season - McCarthy, Brendan (Dance Books Ltd., Alton,Hampshire (UK), 2006)
Exploring the logistics of planning and commissioning a season of performances. In London a dedicated dance audience of critical mass mitigates the effects of competition. PALABRAS CLAVE: the dance performances business, the logistics of planning.